Proclamation five : interpreting the lessons of the Church year - Sloyan, Gerard S., 1919- (Minneapolis : Fortress, 1994)
Discusses appointed lessons for the Day of Pentecost and the Ist through 9th Sundays after Pentecost.
Keywords: Bible -- Homiletical use; Bible -- Liturgical lessons, English; Pentecos Festival -- Sermons -- Outlines, syllabi, etc; Pentecost seasons -- Sermons -- Outlines, syllabi, etc